2022
DOI: 10.1200/jco.21.01506
|View full text |Cite
|
Sign up to set email alerts
|

CALGB 40603 (Alliance): Long-Term Outcomes and Genomic Correlates of Response and Survival After Neoadjuvant Chemotherapy With or Without Carboplatin and Bevacizumab in Triple-Negative Breast Cancer

Abstract: PURPOSE CALGB 40603 ( NCT00861705 ), a 2 × 2 randomized phase II trial, demonstrated that adding carboplatin or bevacizumab to weekly paclitaxel (wP) followed by doxorubicin and cyclophosphamide significantly increased the pathologic complete response (pCR) rate in stage II-III triple-negative breast cancer. We now report long-term outcomes (LTOs) and correlative science end points. PATIENTS AND METHODS The Kaplan-Meier method was used to estimate LTOs in 443 patients who initiated study treatment. Log-rank te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(62 citation statements)
references
References 39 publications
3
47
1
Order By: Relevance
“…A total of 863 studies were identified in the literature search, of which 23 studies were selected for full text review after screening the titles and abstracts. Of these, eight studies [ 8 , 9 , [15] , [16] , [17] , [18] , [23] , [24] , [25] , [26] , [27] , [28] , [29] ] fulfilled the eligibility criteria and were included for qualitative synthesis and meta-analysis, with a total of 2425 patients. ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 863 studies were identified in the literature search, of which 23 studies were selected for full text review after screening the titles and abstracts. Of these, eight studies [ 8 , 9 , [15] , [16] , [17] , [18] , [23] , [24] , [25] , [26] , [27] , [28] , [29] ] fulfilled the eligibility criteria and were included for qualitative synthesis and meta-analysis, with a total of 2425 patients. ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Disease progression under therapy was not considered as an event for DFS. 3 year DFS 85.8% vs 76.1%, HR 0.56 [95%CI 0.34–0.93]; p = 0.024 3 yr OS 91.9% vs 86.0%, HR 0.6, [95%CI 0.32–1.12], p = 0.109 84/158 (53·2%, 54·4–60·9) vs 58/157 (36·9%, 29·4–44·5) OR: 1·94 (1·24–3·04) p = 0.005 Sikov (2016, 2022) CALGB 40603 [ 9 , 29 ] EFS is measured from study entry to ipsilateral invasive breast or locoregional recurrence, distant recurrence or death from any cause RFS in protocol From definitive surgery to first instance of ipsilateral invasive breast tumour recurrence, local/regional invasive breast cancer recurrence, distant recurrence, or death from any cause. Number of Participants who Died Due to Any Cause or had a recurrence.…”
Section: Resultsmentioning
confidence: 99%
“…Survival association analysis for the selected biomarkers were independently investigated using the online tool Kaplan-Meier (KM) plotter 44 . In addition, 1) TCGA paired tumor and normal-adjacent TNBC samples 14 , 2) non-LAR vs. LAR TNBC gene expression cohorts 3) non-LAR gene expression cohorts with respect to pathologic complete response phenotype were also surveyed using publically available gene expression data 3,[45][46][47][48][49] .…”
Section: Statistics and Bioinformatics Analysismentioning
confidence: 99%
“…To determine if there was any clinical correlation with these immune cell subsets, we derived a signature using differentially expressed genes (log Fc>0.03) from the T12 and T11 tams, which are included in Supplemental Table S1. We applied T12 TAM and T11 TAM signatures to two data obtained from stage II-III TNBC patients from the CALGB 40603 trial (35) and the SCAN-B dataset (36).The T12 TAM signature was significantly upregulated in human claudin-low tumors from TNBC patients, while the T11 TAM signature was not specifically associated with these human claudin-low tumors (Fig 7a, 7b, 7c, 7d). Additionally, high expression of the T12 TAM signature was associated with a decreased overall survival in TNBC patients from the SCAN-B dataset (Fig 7e).…”
Section: T12 Tam Signature Is Upregulated In Patients With Claudin-lo...mentioning
confidence: 99%